Assessing the adherence to the current guidelines in the management of syncope patients - Zahra Rahnamoon; Akbar Shafiee; Arash Jalali; Saeed Sadeghian (Shahid Beheshti University of Medical Sciences, 2018)
Background: There exist gaps in the implementation of guideline-recommended treatments and interventions to manage syncope. The present study aimed to investigate the adherence to the current guideline for the diagnosis and management of syncope patients referred to a tertiary center.   Methods: A cross-sectional study was carried out with the study group consisting of 324 consecutive patients, who were diagnosed with unexplained syncope with one or more attacks and were referred for head-up tilt table test (HUTT) between September 2009 and September 2011 to Tehran Heart Center. All the patients underwent a thorough evaluation, including a careful medical history and physical examination as well as a thorough history of all procedures performed before referral. The data collected was compared between patients with positive and negative HUTT results and also based on the referring physician, in order to assess the deviation from syncope guideline in their management. We compared the selected groups using a chi-square test for categorical variables and student t-test or analysis of variance (ANOVA) for continuous variables where appropriate.   Results: A total of 324 patients with a Mean (SD) age of 41.04 (17.74) years were enrolled in the study (158 patients, i.e. 48.8%, were male). HUTT was positive in 181 (55.8%) patients. Brain computed tomography scan and coronary angiography were performed more in the initial assessment of the patients with a negative HUTT compared with patients with negative HUTT (P=0.001 and P=0.01, respectively). Significantly higher rates of brain MRI (P=0.01), brain imaging (P=0.03), and electroencephalography (P=0.002) were observed among the neurologists' referrals while echocardiography (P<0.001), exercise tolerance test (P=0.001), electrocardiogram Holter monitoring (P<0.001), and coronary angiography (P=0.02) were significantly more performed in patients referred by a cardiologist.    Conclusion: We observed a noticeable deviation from the current guideline for the management of syncope although the patients underwent expensive tests with little benefit.